0752 JZP-258 Dose Titration and Transition from Sodium Oxybate in a Placebo-Controlled, Double-Blind, Randomized Withdrawal Study in Adult Participants With Narcolepsy With Cataplexy. (27th May 2020) - Foldvary-Schaefer, N; Bogan, R K; Thorpy, M J; Huang, L; Skowronski, R; Dauvilliers, Y
Abstract: Introduction: Sodium oxybate (SXB) is a standard of care for the treatment of cataplexy and excessive daytime sleepiness in narcolepsy. JZP-258 is an oxybate product candidate (at same concentration as SXB) with 92% less sodium. JZP-258 dose adjustment during titration was evaluated. Methods: At study entry, participants were taking SXB only, SXB+other anticataplectics, anticataplectics other than SXB, or were cataplexy treatment-naive. JZP-258 treatment began during a 12-week, open-label optimized treatment and titration period. Participants taking SXB only or SXB+other anticataplectics transitioned to JZP-258 at the same gram-for-gram dose as SXB and titrated to an efficacious and tolerable (optimal) dose from weeks 3-12. Participants taking other anticataplectics or who were anticataplectic-naive initiated JZP-258 at 4.5 g/night and were titrated to an optimal dose at 1-1.5 g/night/week (maximum total dose, 9 g/night). A 2-week stable-dose period and 2-week, double-blind, randomized withdrawal period followed. Results: During the stable-dose period, total nightly JZP-258 dose (median [range]) was higher in participants taking SXB at study entry (SXB-only, 7.5 g [4.5-9.0], n=45; SXB+other anticataplectics, 9.0 g [6.0-9.0], n=14) compared with those not taking SXB (other anticataplectics, 7.5 g [4.5-9.0], n=23; anticataplectic-naive, 7.0 g [3.0-9.0], n=67), and dose adjustments were fewer. In most (69%) participants taking SXB at study entry who entered the stable-dose period, no change in dose was required (median [range] number of adjustments was 0 ([0-8]); for those with a change in dose, most changes were within one titration step (1.5 g/night). In participants not taking SXB at study entry, the median (range) number of adjustments was 3.0 (0-7). Conclusion: Most participants taking SXB at study entry transitioned to JZP-258 treatment at the same dose with retained effectiveness. Participants not previously taking SXB achieved a tolerable and efficacious dose of JZP-258 after a median of 3 adjustments. Support: Jazz Pharmaceuticals